Infection prevention and control in Indonesian hospitals: identification of strengths, gaps, and challenges - Indri Rooslamiati Supriadi; Cynthia P. Haanappel; Leli Saptawati; Nani H. Widodo; Gortap Sitohang; Yuslely Usman; Ida Bagus Anom; Ratih Dian Saraswati; Michal Heger; Pieter A. Doevendans; Hindra Irawan Satari; Anne F. Voor in ‘t holt; et al. (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background Infection prevention and control (IPC) in hospitals is key to safe patient care. There is currently no data regarding the implementation of IPC in hospitals in Indonesia. The aim of this study was to assess the existing IPC level in a nationwide survey, using the World Health Organization (WHO) IPC assessment framework tool (IPCAF), and to identify strengths, gaps, and challenges. Methods A cross-sectional study was conducted from July to November 2021. Of all general hospitals in Indonesia, 20% (N = 475) were selected using stratified random sampling based on class (A, B, C and D; class D with a maximum of 50 beds and class A with ≥ 250 beds) and region. The IPCAF was translated into Indonesian and tested in four hospitals. Questions were added regarding challenges in the implementation of IPC. Quantitative IPCAF scores are reported as median (minimum–maximum). IPC levels were calculated according to WHO tools. Results In total, 355 hospitals (74.7%) participated in this study. The overall median IPCAF score was 620.0 (535.0–687.5). The level of IPC was mostly assessed as advanced (56.9% of hospitals), followed by intermediate (35.8%), basic (7.0%) and inadequate (0.3%). In the eastern region of the country, the majority of hospitals scored intermediate level. Of the eight core components, the one with the highest score was IPC guidelines. Almost all hospitals had guidelines on the most important topics, including hand hygiene. Core components with the lowest score were surveillance of healthcare-associated infections (HAIs), education and training, and multimodal strategies. Although > 90% of hospitals indicated that surveillance of HAIs was performed, 57.2% reported no availability of adequate microbiology laboratory capacity to support HAIs surveillance. The most frequently reported challenges in the implementation of IPC were communication with the management of the hospitals, followed by the unavailability of antimicrobial susceptibility testing results and insufficient staffing of full-time IPC nurses. Conclusion The IPC level in the majority of Indonesian hospitals was assessed as advanced, but there was no even distribution over the country. The IPCAF in combination with interviews identified several priority areas for interventions to improve IPC in Indonesian hospitals.